Preparedness for the year 2000 : the millennium bug preparedness checklist : (strategic and operational) - W'O Okot-Uma, Rogers (Commonwealth Secretariat LondonGB, 1998)
Provides 'best practice' guidance on the millennium bug. Supplies two chcklist templates for the year 2000 Preparedness at the strategic and operational levels. Provides a rapid assessment questionnaire which will enable member governments to ascertain at a glance the status of their Y2K preparedness.